Disparities in access to anti-HER2 therapies in neoadjuvant chemotherapy: A prognostic analysis based on real-world data comparing Brazil's public and private healthcare systems - Marcelo Antonini; André Mattar; Denise Joffily Pereira da Costa Pinheiro; Isabela Bastos Maia; Marina Diógenes Teixeira; Andressa Gonçalves Amorim; Odair Ferraro; Larissa Chrispim de Oliveira; Marcellus do Nascimento Moreira Ramos; Francisco Pimentel Cavalcante; Felipe Zerwes; Marcelo Madeira; et al. (Breast)
Background: Trastuzumab has significantly improved the treatment of HER2-positive breast cancer, particularly in the neoadjuvant setting, where its combination with chemotherapy increases the pathologic complete response (pCR) rate. This retrospective cohort study assesses the implications of disparities in access to trastuzumab within the Brazilian public healthcare system, focusing on pCR, overall survival (OS) and disease-free survival (DFS) in non-metastatic, HER2-positive breast cancer patients undergoing neoadjuvant chemotherapy (NAC). Methods: The study was conducted in the Hospital Pérola Byington (PEROLA), a public institution, and in the Hospital do Servidor Público Estadual (HSPE), a private institution. pCR was defined as the absence of residual invasive or in situ tumors in the breast and axillary nodes. OS and DFS were calculated by Kaplan-Meier survival analysis for a 5-year period. Results: From 2011 to 2020, 381 patients at PEROLA and 78 at HSPE underwent NAC. Trastuzumab availability was higher at HSPE (83.4 % vs. 60.0 %, p < 0.0001). Use of trastuzumab correlated with significantly higher pCR rates at both the PEROLA (54.3 % vs. 26.4 %, p < 0.0001) and the HSPE (52.7 % vs. 26.4 %, p < 0.0001). HER2-positive patients with pCR at HSPE also had better OS (80 % vs. 61 %, p < 0.0001) and DFS (89 % vs. 67 %, p < 0.0001) compared to those at PEROLA. Conclusion: There were significant differences in the provision of trastuzumab between the public and private healthcare systems, adversely affecting clinical outcomes and patient survival. The current data highlight the pressing need to address equity in cancer treatment to improve prognosis for every patient.